Pooled analysis of routine safety parameters observed in healthy participants at baseline and following placebo administration in early phase clinical studies - Kelly E. Duncan; Runcheng Li; Lata Maganti; Amit Kumar; S. Aubrey Stoch; Geoffrey A. Walford (Wiley, 2024)
Abstract Phase I trials inform on the initial safety profile of a new molecule and impact whether further development is pursued or not. Understanding the effect of non‐pharmacological factors on the variability of routine safety parameters could improve decision making in these early clinical trials, helping to separate signals related to the new molecule from background "noise." To understand the impact of non‐pharmacological factors on routine safety parameters, we evaluated pooled safety data from over 1000 healthy participants treated with placebo in phase I trials between 2009 and 2018. The phase I participants were predominantly men, less than or equal to 50 years, White, and non‐Hispanic; and approximately an equal proportion had body mass index in the normal and overweight/obese range. Following administration of placebo, vital signs, electrocardiogram, and laboratory parameters remained near predose baseline values. Large changes from baseline were observed for many safety parameters, but these occurred in a relatively small number of participants. At least one adverse event (AE) occurred in 49.7% of participants receiving placebo in single ascending dose (SAD) studies and in 72.4% of participants receiving placebo in multiple ascending dose (MAD) studies, with headache being the most commonly reported AE (18.7% in SAD and 28.3% in MAD studies). Overall, these analyses are consistent with non‐pharmacological factors having a small impact on routine safety parameters in a phase I trial. The provided supplemental data may be used to contextualize the magnitude and frequency of abnormal safety values and AEs observed in phase I trials.